Legal Framework of Employing Autonomous Navigation Technologies in Maritime Transport Vessels: Challenges and Benefits from Stakeholder Perspectives - Abdelhady, Mahmoud Abd Elgawwad (Jurnal Cita Hukum, 2024)
The study aims to explore the challenges of employing autonomous navigation technologies in maritime transport vessels by identifying the main challenges and assessing their relation to the readiness of the legislative framework. The methodology conducted for this study is semi-structured interviews to collect data, and participants were recruited via snowball sampling. This method was a series of one-on-one, open-ended interviews with a variety of stakeholders involved in maritime transportation, including "maritime transport experts, technicians, legal professionals, maritime insurance experts, captains, maritime observers, port officials, officials in maritime transport companies, and crew members of maritime transport vessels, along with experts in control and remote sensing systems." Data was gathered in two stages: the first involved in-person and remote interviews focused on exploring the challenges and benefits of employing autonomous navigation technologies in maritime transport vessels. In the second stage, the main challenges identified in the first round were presented again to the experts to evaluate their impact on the readiness of the legislative framework. The methodology ensured sufficient data collection, reaching a saturation point, which enhanced the reliability of the results. The study's results confirm the strong relationship between overcoming the challenges facing autonomous navigation technologies in maritime transport vessels and utilising these technologies. It also confirms the direct impact of the expansion of autonomous navigation technologies on the legal status of the ship and maritime navigation personnel. This entails the need for innovative standards to ensure safety and determine legal responsibilities in line with the unique risks associated with autonomous navigation technologies. The study offers a distinctive contribution by exploring the challenges of employing autonomous navigation technologies in maritime transport vessels and analysing the challenges and benefits from multiple, realistic perspectives. This contributes to creating a suitable environment for employing autonomous navigation technologies in maritime transport vessels, achieving the benefits of these technologies, and overcoming the challenges.